Preconcentration strategies in the processing of nickel laterite ores part 2: Laboratory experiments. (August 2015) - Quast, Keith; Connor, Jason N.; Skinner, William; Robinson, David J.; Li, Jian; Addai-Mensah, Jonas
Highlights: Various physical separation techniques are only applicable to small scale evaluation. Physical separation techniques have been tested on Australian Ni laterites. Roasting goethitic laterite can increase Ni and Co recovery by magnetic separation. Complex mineralogy compromises significant Ni laterite ore upgrading. Abstract: A number of physical separation techniques for nickel (Ni) laterites have been investigated at laboratory and pilot plant scale and reported in the open literature. These included sink–float (or dense media) separation, gravity separation, magnetic separation, electrostatic separation, (roasting) and flotation. The information located so far and reported in the literature review by Quast et al. (2015) suggests that all these techniques, although providing some degree of upgrading, have not been incorporated into full plant operations as yet. The only successful preconcentration technique incorporated into some commercial operations has been the removal of a coarse product containing lower Ni values than the feed. In this work, the application of a number of physical separation techniques (screening, gravity and magnetic separation with and without roasting) has been investigated in the laboratory for upgrading three Western Australian low-grade Ni laterites (goethitic, siliceous goethitic and saprolitic). Roasting of the goethitic laterite caused a noticeable increase in Ni and Co (and corresponding mass) recovery into the magnetic product with temperature up to a certain point, but this effect was reversed at 650 °C. Overall, the application of the selected techniques failed to produce any significant Ni grade enhancement for these three laterite ores. These tests confirm that the complex mineralogy of these three Ni laterite ores compromises any significant upgrading in Ni values by standard physical separation techniques.